A Cross-Sectional Study of Assessment of Predominance of Prakrutiamong Patients with Diabetic Neuropathy in Wardha City: Life Sciences-Ayurveda - Jaiswal, Gargi; Sawarkar, Dr. Punam; Sawarkar, Dr. Gaurav; Verma, Dr.Shubham (International Journal of Life Science and Pharma Research, 2023)
India is a developing country, so much of the Indian subcontinent are converting into urban areas, which lead to changes in lifestyle involving major tourist in battery plateau physical activities and increasing mental stress, which leads to insulin inertia. Approximately 246 million people worldwide have diabetes mellitus. It is estimated that 20 to 30 million people globally suffer from symptomatic diabetic neuropathy. The prevalence of diabetic neuropathy also rises over time. If type 1 diabetes is not well controlled, severe diabetic polyneuropathy and poor glycemic control can appear in young adults just a few months after the disease manifests. Ayurveda can be correlated with MajjaDhatuDushti (Structural and functional defects of neurons). Identification of the predominance of a specific type of Prakrutiin patients with diabetic neuropathy in Wardha City. The prime objectives of the present study are to find out the predominance of specific Prakriti in patients with diabetic neuropathy in Wardhacity&create awareness in them regarding complications of Diabetes mellitus, especially diabetic neuropathy and its relation with Prakruti. The current study was a cross-sectional study based on a personal interview of patients and Prakrutiquestionnaires. It occurred at Salod(H), Wardha, Maharashtra’s Mahatma Gandhi Ayurved College, Hospital & Research Center. It was found that the prevalence of diabetic neuropathy is high in PittajPradhanVataPrakruti. In this present study, most of the affected patients were male. The present study concludes that diabetic neuropathy was found more prevalently in patients with Pitta PradhanVataPrakruti. Specific lifestyle modifications can be recommended for patients with Prakriti, as mentioned earlier, to prevent diabetic neuropathy in the future. Keywords: , , , ,